Blocking autophagy flux promotes interferon-alpha-mediated apoptosis in head and neck squamous cell carcinoma. (1st June 2019) - Yang, Wenyi; Jiang, Chunlan; Xia, Weiya; Ju, Houyu; Jin, Shufang; Liu, Shuli; Zhang, Liming; Ren, Guoxin; Ma, Hailong; Ruan, Min; Hu, Jingzhou
Abstract: Despite multiple antitumor activities, interferon-alpha (IFNα) therapy alone is less effective in solid tumors. Autophagy has been reported to play a key role in tumor chemoresistance. Therefore, it is meaningful to explore whether autophagy can be activated by IFNα in head and neck squamous cell carcinoma (HNSCC) and serve as a potential target to improve efficacy of IFNα therapy. In this study, we report that IFNα not only exhibits anti-proliferation activity and induces apoptosis, but also activates autophagy in HNSCC cells. Moreover, silencing autophagy-related protein 5 (ATG5) and signal transducer and activator of transcription 1 (STAT1) suppresses autophagy flux. Furthermore, IFNα and autophagy inhibitors (hydroxychloroquine and wortmannin) show clear synergistic effects on inhibiting growth and promoting apoptosis in HNSCC cells and xenograft models. Our findings indicate that IFNα-induced autophagy plays a cytoprotective role and blocking autophagy flux promotes IFNα-mediated apoptosis in HNSCC. These results suggest that the combination of IFNα and autophagy inhibitors represents a novel strategy for HNSCC treatment. Highlights: IFNα induces autophagy in HNSCC cells and xenografts models. ATG5 and STAT1 are required for IFNα-induced autophagy in HNSCC cells. IFNα and autophagy inhibitors show synergistic antitumor effect in vitro and in vivo.